Observation on the Efficacy of Ginkgo Ketone Ester Drop Pill in Improving Hypertension Combined with Carotid Atherosclerotic Plaque - Jie Zhang; Yingli Ma (Emergency Medicine International)
Purpose. To observe and analyze the efficacy of Ginkgo ketone ester drop pill intervention in patients with hypertension combined with carotid atherosclerotic plaque. Methods. The subjects were 300 patients with hypertension complicated with carotid atherosclerotic plaque treated in our hospital from January 2019 to September 2021. The grouping was done by the random number table method and 300 patients were divided equally into 2 groups. One group was treated with Western medicine alone (clopidogrel sulfate tablets, phenyl amlodipine tablets, irbesartan tablets, and resorvastatin) as the Western medicine group (WM group, n = 150), and one group was added to this intervention with Ginkgo ketone ester drop pill as the Chinese medicine group (CM group, n = 150). The observation indexes were the improvement of blood pressure (systolic blood pressure (SBP) and diastolic blood pressure (DBP)), blood lipids (low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglyceride (TG), and total cholesterol (TC)), vascular endothelial function (nitric oxide (NO) and endothelin-1 (ET-1)), inflammatory factors (C-reactive protein (CRP) and interleukin-6 (IL-6)), plaque (intimal medial thickness (IMT) of carotid artery and plaque area), and efficacy after intervention and adverse effects during intervention in both groups. Results. After intervention, SBP, DBP, LDL-C, TG, and TC levels were lower and HDL-C levels were higher in both groups than before intervention in the same group, and both CM groups improved significantly compared with the WM group (P<0.05). After intervention, NO levels were higher and ET-1 levels were lower in both groups than before the intervention in the same group, and both CM groups improved significantly compared with the WM group (P<0.05). After intervention, CRP and IL-6 levels were lower in both groups than before intervention in the same group, and both CM groups improved significantly compared with the WM group (P<0.05). After intervention, IMT and plaque area were lower in both groups than before intervention in the same group and both CM groups improved significantly compared with the WM group (P<0.05). The total effective number of the CM group was better than the WM group (P<0.05), and there was no significant difference in the adverse reactions number in both groups (P>0.05). Conclusions. The treatment of hypertension combined with carotid atherosclerotic plaque with Ginkgo ketone ester drop pill helps to improve the blood pressure, blood lipid, and vascular endothelial function of patients and helps to inhibit the inflammation level and atherosclerotic plaque of patients, with significant efficacy and no significant adverse effects in patients, which is worthy of clinical promotion.